Effects of STZ-Induced Diabetes on the Relative Weights of Kidney, Liver and Pancreas in Albino Rats: A Comparative Study - Muhammad Zafar; Syed Naeem‐ul‐Hassan Naqvi (2010)
We studied the effects of streptozotocin (STZ)-induced diabetes on the body weights of animals and the relative weights of kidney, liver and pancreas in albino rats.The aim of the study was to find an association between the reduction in the body weights of diabetic animals and the relative weights of kidney, liver and pancreas in proportion to the body weight of animals in albino rats.This study was performed in the Department of Anatomy and Institute of Pharmaceutical Sciences, Baqai Medical University, Karachi and Pathology department of College of Physicians & Surgeons (CPSP) Pakistan in 2007-08.Diabetes was induced by a single dose of STZ (45 mg/kg, b.w.) given intraperitoneally in sodium citrate buffer at pH 4.5.Eighty albino rats were divided into five groups: control (A) and STZ treated (B, C, D, and E) which were sacrificed 2, 4, 6 and 8 weeks post treatment respectively.All the animals were weighed prior to the administration of streptozotocin and at sacrificial time.Kidney, liver and pancreas were removed, dried and weighed on Sartorius balance.The body weights of animals in different groups changed at variable time intervals.The Kidney weight was significantly increased, liver weight was slightly increased while the weight of pancreas was unaffected when compared with the weight of diabetic animals.It seems that the STZ-induced diabetes causes a significant reduction in the body weight of diabetic animals while the relative weights of kidney and liver were increased and the weight of pancreas was unaffected.